Uncertainty quantification of semi-destructive testing for chloride content assessment for a concrete bridge in maritime environment - Schoefs, Franck; Awa Zahui Raissa, Keita; Bonnet, Stephanie; O’Conor, Alan John (Frontiers in Built Environment, 2023)
Harbors play a major socio-economic role in almost all littoral countries with more than 80% of trade exchange and play also usually a key role for military defense. Reinforced Concrete (RC) structures in harbors are designed for a long time (50 to 70 years) and are subjected to chloride-induced corrosion. Diagnosis usually relies on inspections which consist in Semi-Destructive Testing (SDT) with large uncertainties. Uncertainties may lead to a bad diagnosis, and bad decisions as a consequence. This paper aims at providing a probabilistic model for this error of measurement. This assessment is performed through multiple measurements on the same cores extracted from an existing bridge. There are carried out by 3 operators using 2 published protocols. A total of 566 measurements is available. The effect of the operator and the protocols are discussed and then modelled. It is concluded that the error of measurement depends the chloride content. The effect of this error on the diagnosis is then illustrated.